Socio-environmental challenges in the development of geothermal power plants in Geothermal Island - Andre Bonardo Yonatan Sitorus (Bioculture Journal, 2026)
Background: Indonesia’s geothermal expansion is positioned as a flagship pathway to its net zero commitment, with Flores Island legally designated as Pulau Panas Bumi (Geothermal Island). Yet existing scholarship on geothermal transitions remains anchored in Java-centric, technocratic evaluations of policy and emission targets, leaving the spatial, hydrological, and procedural injustices unfolding in populated, semi-arid, customary landscapes systematically under-examined. This study analyses the socio-environmental challenges of geothermal expansion in Flores through a political ecology framework, mobilising the theses of conservation and control, environmental conflict and exclusion, and formation of environmental subjects. Methods: A desk-based mixed-methods design integrates GIS intersection analysis of 6 Geothermal Working Areas (WKPs) with critical watersheds and BRWA-mapped customary territories, alongside a directed thematic analysis of 184 coded quotations extracted from 40 Dewan Pers-verified media reports and civil-society publications (2017–2026). Findings: Six WKPs occupy 7.3% of Flores' landmass and overlap 18 critical watersheds in a semi-arid agrarian setting; WKP Sokoria entirely engulfs the 583.56-hectare verified Kawasan Adat Nua Saga, while WKP Oka Ile Ange enclosed 51% of Kawasan Adat Lewolema. Discourse analysis reveals that 70% of state voice concentrates in only 4 elite figures, while community resistance disperses across 28 grassroots actors centred on water and livelihood loss. The integration of spatial enclosure, procedural FPIC failure, and discursive delegitimization operate as systemic structural violence rather than implementation friction. Conclusion: Flores's geothermal transition reproduces extractive logics under a green vocabulary, constituting green colonialism rather than environmental justice. Achieving a genuinely just transition requires restructuring national spatial governance, legally protecting indigenous territories from overarching strategic mandates, and enforcing substantive FPIC to prevent the exclusionary capture of local socio-ecological systems. Novelty/Originality of this article: This study reframes Java-centric geothermal expansion by demonstrating how green energy deployment in semi-arid customary islands operates as systemic structural violence and spatial green colonialism.